2009
DOI: 10.1021/ef900337g
|View full text |Cite
|
Sign up to set email alerts
|

Production and Evaluation of Biodiesel from Field Pennycress (Thlaspi arvenseL.) Oil

Abstract: Field pennycress (Thlaspi arVense L.) oil is evaluated for the first time as a feedstock for biodiesel production. Biodiesel was obtained in 82 wt % yield by a standard transesterification procedure with methanol and sodium methoxide catalyst at 60 °C and an alcohol to oil molar ratio of 6:1. Acid-catalyzed pretreatment to reduce the acid value of crude field pennycress oil resulted in a yield after methanolysis of 94 wt %. Field pennycress oil had high contents of erucic (13(Z)-docosenoic; 32.8 wt %) and lino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
174
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(183 citation statements)
references
References 36 publications
6
174
1
2
Order By: Relevance
“…In the US Midwest, pennycress is being developed as a winter-hardy oilseed crop that can be double-and relay-cropped to diversify agroecological systems presently dominated by the summer-annual crops maize and soybean (Moser et al, 2009;Phippen and Phippen, 2012). Pennycress possesses many traits that can support its integration in existing maize-soybean agroecological systems.…”
Section: Field Pennycress -A Promising Vehicle For Diversificationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the US Midwest, pennycress is being developed as a winter-hardy oilseed crop that can be double-and relay-cropped to diversify agroecological systems presently dominated by the summer-annual crops maize and soybean (Moser et al, 2009;Phippen and Phippen, 2012). Pennycress possesses many traits that can support its integration in existing maize-soybean agroecological systems.…”
Section: Field Pennycress -A Promising Vehicle For Diversificationmentioning
confidence: 99%
“…Additionally, seedpods shatter only a few weeks after maturity, which results in a narrow harvesting window and can result in large yield losses. Finally, pennycress seed contains levels of glucosinolate compounds that may be harmful to livestock (Moser et al, 2009).…”
Section: Sustainability Standards For Production Of Pennycress Productsmentioning
confidence: 99%
“…Međutim, korišćenje jestivih ulja u procesima dobijanja biodizela ograničavaju njihova primarna primena u ljudskoj ishrani i visoka cena. S obzirom da u ukupnoj ceni proizvodnje biodizela uljne sirovine imaju najveći udeo [3,4], poslednjih godina pažnju istraživača privlači ispitivanje mogućnosti primene novih i jeftinijih ulja kao što su ulja dobijena iz semena različitih korovskih biljaka: etiopijska slačica (Brassica carinata) [5], kravlja trava (Thlaspi arvense L.) [6], bela slačica (Sinapis alba) [7], tatula (Datura stramonium) [8], konopljica (Euphorbia lathyris L.), pileće drvo (Sapium sebiferum L.) i barbadoski orah (Jatropha curcas L.) [9].…”
Section: Uvodunclassified
“…Homogenous base-catalyzed transesterification of CSO provided the methyl esters (CSME) in high yield (96 wt%) employing classic conditions described previously [8,13,[21][22][23][24][25]. The AV of crude CSO (2.71 mg KOH/g) was prohibitively high for direct methanolysis.…”
Section: Preparation Of Cottonseed Oil Methyl Esters and Fuel Propertiesmentioning
confidence: 99%
“…Free fatty acids react with homogenous base catalysts such as sodium methoxide to form soap (sodium salt of FA) and methanol (or water in the case of sodium hydroxide), thus irreversibly quenching the catalyst and reducing product yield [8,26]. Therefore, sulfuric acid-catalyzed pretreatment of crude CSO with methanol was conducted prior to base-catalyzed transesterification to reduce the AV to 0.53 mg KOH/g utilizing reaction conditions described previously [24,25]. Optimization of CSME yield using techniques such as response-surface methodology was considered beyond the scope of the current study, but is reported in refs.…”
Section: Preparation Of Cottonseed Oil Methyl Esters and Fuel Propertiesmentioning
confidence: 99%